2021
DOI: 10.3390/jcm10020305
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Eosinophil Recovery in COVID-19: A Multicentre, Retrospective Cohort Study on Patients Hospitalised in Spanish Hospitals

Abstract: Objectives: A decrease in blood cell counts, especially lymphocytes and eosinophils, has been described in patients with serious Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), but there is no knowledge of their potential role of the recovery in these patients’ prognosis. This article aims to analyse the effect of blood cell depletion and blood cell recovery on mortality due to COVID-19. Design: This work was a retrospective, multicentre cohort study of 9644 hospitalised patients with confirmed C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Consistently, the ICU metastasis rate was significantly higher in the eosinopenia group than in the non-eosinopenia group ( 31 ). Moreover, eosinophil reduction has been reported in patients with SARS-CoV-2 infection, which can be improved when the viral load in patients is reduced ( 27 , 32 ), and a study have shown that the recovery of eosinophils has independent prognostic value for the course of mild diseases ( 33 ). One study tested the hypothesis that the decrease in eosinophils was associated with a malfunction of the innate immune response, and found that the decrease in eosinophils was specific for COVID-19 ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the ICU metastasis rate was significantly higher in the eosinopenia group than in the non-eosinopenia group ( 31 ). Moreover, eosinophil reduction has been reported in patients with SARS-CoV-2 infection, which can be improved when the viral load in patients is reduced ( 27 , 32 ), and a study have shown that the recovery of eosinophils has independent prognostic value for the course of mild diseases ( 33 ). One study tested the hypothesis that the decrease in eosinophils was associated with a malfunction of the innate immune response, and found that the decrease in eosinophils was specific for COVID-19 ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship was demonstrated between the number of eosinophils and the mortality rate. Scientists have shown that an increase in the number of peripheral blood eosinophils has a positive effect on prognosis and lowers the mortality rate (OR) [ 17 ]. Mao et al, in their study, assessed the effect of the number of eosinophils on the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] In surviving acute lung injury patients, the number of eosinophils in the lungs showed an increased compared to the non-survivors. [ 40 ] Similarly, the number of peripheral blood eosinophils also increased in surviving acute respiratory distress syndrome patients. Therefore, the scholars further investigated its molecular mechanism and found that in the initiation of acute lung injury, CD101 − eosinophils increased more rapidly and briefly than the neutrophils and secreted Protectin-D1 through Alox15-mediated to reduce the accumulation of inflammatory cells and reduce inflammatory factors, thus playing a role in fighting lung inflammation.…”
Section: Discussionmentioning
confidence: 99%